Dual Emission of meso‐Phenyleneethynylene–BODIPY Oligomers: Synthesis, Photophysics, and Theoretical Optoelectronic Study. Issue 7 (22nd December 2020) - Flores, J. Reyes; Castruita‐De León, Griselda; Turlakov, Gleb; Arias, Eduardo; Moggio, Ivana; Montemayor, Sagrario M.; Torres, Román; Ledezma, Raquel; Ziolo, Ronald F.; González‐Torres, Julio
Abstract: Two series of 2, 5‐di(butoxy)phenyleneethynylenes, one halogenated ( n PEC4‐X ; n =2, 3, or 4) and the other boron‐dipyrromethene (BODIPY) terminated ( n PEC4‐By ; n =3, 4, or 5; By=BODIPY), were synthesized monodirectionally by the step‐by‐step approach and the molecular structure was corroborated by NMR spectroscopy ( 1 H, 13 C‐DEPTQ‐135, COSY, HSQC, HMBC, 11 B, 19 F) and MALDI‐TOF mass spectrometry. The multiplicity and J ‐coupling constants of 1 H, 11 B, and 19 F/ 11 B NMR signals revealed, in the n PEC4‐By series, that the phenyl in the meso position of BODIPY becomes electronically part of the conjugation of the phenyleneethynylene chain, whereas BODIPY is electronically isolated. The photophysical, electrochemical, and theoretical studies confirm this finding because the properties of n PEC4‐By are comparable to those of the n PEC4‐X oligomers and BODIPY, indicating negligible electron communication between BODIPY and the n PEC4 moieties. Nevertheless, energy transfer (ET) from n PEC4 to BODIPY was rationalized by spectroscopy and theoretical calculations. Its yield decreases with the n PEC4 conjugation length, according to the increase in distance between the two chromophores, resulting in dual emission for the longest oligomer in which ET is quenched. Abstract : Double DIPY : meso ‐Phenyl‐derived boron‐dipyrromethene (BODIPY), coupled to phenyleneethynylene (PE) oligomers, is electronically isolated from the π‐PE conjugation because of its orthogonality, but displays high energy transfer (ET) efficiencies or dual emission.